Formulation of preferences of murabahah, wadi'ah in non-Muslim Community in the Indonesian Sharia Branch - Hadi, Muhammad (IAIN Kendari, 2021)
Research Titled Formulation of preferences of murabahah, wadi'ah in non-Muslim Community in the Indonesian Sharia Branch, Bertuju to find out the accadi especially for non-Muslim customers at Bank Syariah Indonesia BSI. In this study, there are similarities in service and financing, although somewhat different in the implementation of the agreement, the ban on non-Muslim ban in BSI only uses the acad, Or Voting for the financing of murabahah and wadi'ah selected, especially the product savings of Hesiah. The study uses quantative approaches and observer methods, interviews, documentation and triangulation of primary data. The results of the study, concluded the buzz using Madasid theory aI-shariah imam Shatibi, especially in wildul malls by understanding direct view of non-Muslim bans related to deposits in BankSyariah Indonesia. There are several invoices, fulfilling the interests of non-Muslim banners; in the interpretation of behavior.trust, Honesty and Transparent in the Bank. Results From Some responding to non-Muslims also indicate that the same understanding of Muslim-non-Muslim stars in BSI banks in the unworthy profit system, although different in the applicability of the accadnon-Muslim customers need to act as in Islam, in addition to being limited in choosing products savings murabalah and wadi'ah in Islamic bank Indonesia. In this study, there is also no illustration of moderation behavior in service means not distinguishing between Muslims and non-Muslims, not being extreme even if prioritizing to any customer who comes in the branch of in the Indonesian Sharia Branch.